Coastal Habitat Suitability of Kade Tigo, Tapanuli Tengah for Marine Ecotourism - Sinaga, Nella Asima Br.; Samiaji, Joko; Tanjung, Afrizal (Journal of Coastal and Ocean Sciences, 2023)
This research was carried out in February – May 2022 at Kade Tigo Beach, Central Tapanuli. This study aims to determine the suitability value and carrying capacity of Kade Tigo Beach for sustainable marine ecotourism. The method used is a survey method with the determination of research stations by purposive sampling. Based on the study's results, an average travel suitability index value was obtained of 88% and was categorized in the very appropriate category. The carrying capacity of the Kade Tigo Beach area is 9,000 people a day, 270,000 people a month, and 3,285,000 a year